The Sulphide Ores of Copper. Some Results of Microscopic Study. (431c11c8-2185-4af9-9837-4390a6ba9294) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1913)
Discussion of the paper of L. C. Graton and Joseph Murdoch, presented at the New York Meeting, February, 1913, and printed in Bulletin No. 77, May, 1913, pp. 741 to 797. THOMAS T. READ, New York, N. Y. (communication to the Secretary *) :-At the meetings of English technical societies it not infrequently happens that, during the discussion of a paper, someone will arise to say that although he highly appreciated the material presented, nevertheless he believed it would have been better if some other phase of the question had been more highly emphasized. Assuming that this form of discussion is permissible in the Institute, I should like to reiterate the point made by Prof. A. J. Moses that conclusive proof of the identity of the minerals in question is an essential feature of the study of ores in this way. This is also expressed by Paul Krusch in his recent valuable paper 1 on the sulphide ores (in which he arrives at conclusions diametrically opposed to those of Mr. Graton), as follows : ?The diagnostic properties of the various ore minerals are known to but a limited circle of investigators." Many earlier investigators began the study of ores beneath the microscope by reflected light, but discontinued their work, in most cases, because they were unwilling to undertake the great amount of preliminary work necessary to securely establish a basis for their inferences. It is evident that Messrs. Graton and Murdoch realize that the promised later paper on diagnostic characters will be the more important of the two, but the point should be emphasized to forestall a flood of literature from other investigators who may gain the impression that the brief survey of polished specimens is a wade mecum to incontrovertible conclusions as to any given ore deposit.